Evolution of Citrus Disease Management Programs and Their Economic Implications: The Case of Florida’s Citrus Industry - Ronald P. Muraro (EDIS)
Managing new exotic endemic diseases is very costly, and it is imperative that state and federal governments focus on preventing the introduction of other diseases such as citrus variegated cholorosis and citrus leprosis virus. This 6-page fact sheet focuses on the expanded costs of managing exotic citrus diseases as they become endemic or established within a citrus industry. Written by Ronald P. Muraro and published by the UF Department of Food and Resource Economics, October 2012.